PALEOGEOGRAPHIC ASPECTS OF BURIMSKA SUITE FORMATE IN THE KANIV REGION - Menasova, A.; Tymchenko, Yu. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Research of Cretaceous epeiric sea deposits is important for understanding of sedimentation features in that period. The rocks, which were formed during the Albian and Cenomanian time, are particularly interesting. The Albian and Cenomanian deposits are widely represented in the sedimentary cover of Ukraine. These deposits are characterized by fixed lithological composition and numerous fossils are characteristic of these sediments. The Albian and Cenomanian of the Kaniv region are known as the Burimska suite. Goal of the work was to reconstruct the Late Albian – Early Cenomanian paleogeographic sedimentary conditions in the Kaniv region. In order to do that, published data were used alongside with the results of own observations: samples of rocks were selected and studied by the traditional paleogeographic methods. During the Late Albian, the area was covered with the shallowest part of warm shelf sea with normal salinity and was the northern margin of the Tethys. The sedimentary regime of the basin was controlled, on the first place, with the great amount of the terrigenous material coming from an ajoining land. The sediment enriched with silica got into the sea basin as a result of the denudation of the Ukrainian Shield. Obviously, the vegetation cover, which was represented by coniferous gymnosperms, could not resist the denudation. The dependence between accumulation of the silicious deposit and glauconite genesis on the one hand, and biochemical barriers existed on the land-sea boundary, on the other hand, has been established for this epeiric sea which were formed on the sea-land boundary, under the oxidative condition, on the contact of waters with different biochemical parameters (river-sea). This fact allows us to shed a light on the facies conditions of the sedimentation of the Вurimska suite and temporary formations. These results can be the basis for a comparative analysis of the sedimentary environments in the Early-Late Cretaceous for different regions of Ukraine.
Keywords: paleogeography; Cretaceous Period; Burimska suite; Kaniv region